CAUSES OF VISUAL IMPAIRMENT (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the causes of visual impairment, their types and their impact on child development from a scientific and pedagogical perspective. The study covers the effects of congenital and acquired factors of visual impairment, including hereditary diseases, pathologies during pregnancy, infectious diseases, traumas and environmental factors on visual function.